Effects of functional-task training on older adults with Alzheimer's disease - Pedroso, Renata V. [UNESP]; Ayán, Carlos; Fraga, Francisco J.; Da Silva, Thays M. V.; Cancela, José M.; Santos-Galduròz, Ruth F. [UNESP] (Human Kinetics, 2018)
The aim of this study was to verify the effects of functional-task training on cognitive function, activities of daily living (ADL) performance, and functional fitness in community-dwelling older adults with diagnosis of Alzheimer's disease (AD). A total of 57 participants (22 functional-task training group [FTG], 21 social gathering group [SGG], 14 control group [CG]) were recruited. Participants in both intervention groups carried out three 1-hr sessions per week of a functional-task program and social gathering activities for 12 weeks. Significant improvements were observed in executive functions (TMT, t-test, p = .03) in the SGG and in upper limb strength (arm curl, t-test, p = .01) in the FTG. Functional-task training has no significant effect on cognitive function, ADL, and functional fitness among people with AD, although it may contribute to slowing down the process of deterioration this illness causes.
Keywords: Activities of daily living; Cognition; Dementia; Exercise; Functional fitness